5(f) + 3(f) =-1(f + 3)
5f + 3f2 = -f-3
3f2 + 5f + f + 3 = 0
3f2 + 6f + 3 = 0

5(f2 + 2) -3f(3 - 3) = 3f(3 - f)
5f2 + 10 - ...
f(-f+3)+7f(3-f)=f(6-4f)-3
-f2+3f+21f-7f2=6f-4f2-3
-f2-7f2+4f2+3f+21f-6f+3=0
-4f2+18f+3=0/-1
4f2-18f-3=0
-f-(f-f)+8(4-f2)=2...
f(f-4)+(3-f)(3+f)=2(f-3)2
f2-4f (3-f)(3+f)=2(f-3)(f-3)
f2-4f+9+3f-3f-f2=(2f-6)(f-3)
f2-4f+9+3f-3f-f2=2f2-6f-6f+18
f2-f2-2f...
FIN DE LOS EJEMPLOS
:3
Ejemplos de reducción de términos
Upcoming SlideShare
Loading in …5
×

Ejemplos de reducción de términos

133
-1

Published on

Published in: Education
0 Comments
0 Likes
Statistics
Notes
  • Be the first to comment

  • Be the first to like this

No Downloads
Views
Total Views
133
On Slideshare
0
From Embeds
0
Number of Embeds
0
Actions
Shares
0
Downloads
1
Comments
0
Likes
0
Embeds 0
No embeds

No notes for slide

Ejemplos de reducción de términos

  1. 1. 5(f) + 3(f) =-1(f + 3) 5f + 3f2 = -f-3 3f2 + 5f + f + 3 = 0 3f2 + 6f + 3 = 0 5(f2 + 2) -3f(3 - 3) = 3f(3 - f) 5f2 + 10 - 9f + 9f = 9f + 3f2 5f2 - 3f2 - 9f + 9f - 9f + 10 = 0 2f2 - 9f + 10 = 10 5f(f + 2f) -3(f2 - 3f) = 2(-4f + 5f) -1 5f2 + 10f2 - 3f2 + 9f = -8f + 10f - 1 5f2 + 10f - 3f2 + 9f + 8f - 10f + 1 = 0 12f2 + 7f + 1 = 0 -5(f-f)+6f(f-2f)=4(f+4f) -5f+5f+6f2-12f2=4f+16f 6f2-12f2-5f+5f-4f-16f=0 -6f2-20f=0/-1 6f2+20f=0
  2. 2. f(-f+3)+7f(3-f)=f(6-4f)-3 -f2+3f+21f-7f2=6f-4f2-3 -f2-7f2+4f2+3f+21f-6f+3=0 -4f2+18f+3=0/-1 4f2-18f-3=0 -f-(f-f)+8(4-f2)=2f(f-2f) -f-f+f+32-8f2=2f2-4f2 -8f2-2f2+4f2-f-f+f+32=0 -6f2-f+32=0/-1 6f2+f-32=0 1-(8-f)(f+7)-f(3+4f)=-3(7f) 1(-8+f) (f+7)-3f-4f2=-21f 1-8f-56+f2+7f-3f-4f2=-21f f2-4f2-8f+7f-3f+21f+1-56=0 -3f2+11f-55=0/-1 3f2-11f+55=0
  3. 3. f(f-4)+(3-f)(3+f)=2(f-3)2 f2-4f (3-f)(3+f)=2(f-3)(f-3) f2-4f+9+3f-3f-f2=(2f-6)(f-3) f2-4f+9+3f-3f-f2=2f2-6f-6f+18 f2-f2-2f2-4f+3f-3f+6f+6f+9-18=0 -2f2+8f-9=0/-1 2f2-8f+9=0 -3(4-f2)(4-f)-9(f-a)2=-2(f)-3 (-12+3f2)(4+f)-9(f-4)(f-4)=-2(f)-3 -48-12f+12f2+3f3 (-9f+36)(f-4)=-2(f)-3 -48-12f+12f2+3f3-9f2+36f +36f-144=-2f-3 3f3+12f2-9f2-12f+36f+36f+2f-48-144+3=0 3f3+3f2+62f-189=0 -9(9f2-7f)-8(-f+2f)+3f(f+f2)=-1(8f+3f)(8f+3f)+(2f-f) -81f2+63f+8f-16f+3f2=1(-8f-3f)(8f+3f)+2f-f -81f2+63f+8f-16f+3f2+3f2=1-64f2-24f2-9f2+2f-f 3f3-81f2+3f2+64f2+24f2+24f2+9f2+63f+8f-16f-2f+f-1=0 3f3+43f2+54f-1=0
  4. 4. FIN DE LOS EJEMPLOS :3
  1. A particular slide catching your eye?

    Clipping is a handy way to collect important slides you want to go back to later.

×